2017
DOI: 10.1080/20548923.2017.1384175
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and microanalytical study on Sasanian metal objects from Western Iran: A case study

Abstract: Recent archaeological excavation in western Iran discovered a Sasanian palace called Ghaleh Guri (Qela Gowri) beside of the Seimarreh River. As part of the archaeometric studies on the site, five metallic objects (a coin, a disc, a vessel, a decorated strip and some pieces with no specific function) were sampled and analysed using OM and SEM-EDS to determine alloy composition and microstructure. The results showed that strip is made of copper, disc, vessel and unidentifiable object are tin bronze and the coin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
1
12
2
Order By: Relevance
“…%) in comparison to the dark phase (14 wt.%). These results are in good agreement with the earlier studies [10]. The copper-silver alloy phase diagram is shown in figure 6.…”
Section: Microscopic Examination Microstructural Examinationsupporting
confidence: 93%
See 4 more Smart Citations
“…%) in comparison to the dark phase (14 wt.%). These results are in good agreement with the earlier studies [10]. The copper-silver alloy phase diagram is shown in figure 6.…”
Section: Microscopic Examination Microstructural Examinationsupporting
confidence: 93%
“…It has been observed that debased silver with different amounts of copper has been a metallurgical tradition to fabricate silver coins during the Sasanian period. Microstructural analysis of the silver-copper coin showed the casted structure with no additional working or minting [10]. However, a microstructural study of the sasanian silver coins indicates the evidence of mechanical operations along with annealing treatment as observed in other samples, which may suggest pre-heating of the primary silver before minting [9].…”
Section: Fig 4 Xrd Pattern Of Different Coins (A) Coin No 3 and (B) Cmentioning
confidence: 84%
See 3 more Smart Citations